Comercialización de maíz amarillo seco en la zona de Mocache - Villasagua Painii, Jeremias Josua (2022)
The present investigation analyzes and describes the marketing of dry yellow maize in the area of Mocache. There are marketing problems, which are economically damaging to producers. For its execution, a research was carried out, compiled of texts, presentations, congresses, scientific articles and virtual pages, submitted to techniques of analysis, synthesis and paraphrasing about the commercialization of dry yellow maize and its generalities. The topic of marketing dry yellow corn is a factor of great importance to take into account, even more so, if we consider that Mocache is one of the maize zones of the province of Los Rios, therefore, the marketing of this grain and the factors involved are sufficient cause to develop this document. The information gathered gives us conclusions that it is of the utmost importance that government agencies establish policies for marketing maize; farmers in the area should seek partnership among themselves to have a common strengthening, and seek the opening or reopening of collection centers; strategies to reduce high dependence on external inputs need to be identified and implemented; and last but not least, there is no promotion of sustainable production of agroecosystems.